Consultative Workshop on the Development and Implementation of the National Framework for Climate Services for IGAD and SADC Countries: Challenges and Opportunities - Recha, John W.M.; Demissie, Teferi Dejene; Solomon, Dawit; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The Global Framework of Climate Services (GFCS) was developed to enhance resilience in social, economic, and environmental systems to climate variability and change at national and regional levels. Conceived as the national declinations of the GFCS, the National Framework for Weather, Water and Climate Services (NFWWCS), which is used interchangeably in this concept note with the National Framework for Climate Services (NFCS) was introduced at the national level to serve as the national mechanisms to bridge the gap between the climate information being developed by scientists and service providers and the practical needs of users, from global to community levels. For such a Framework to be attained at the national level, however, national stakeholders must drive the process and its design in a manner that addresses national needs and priorities in weather, water and climate service provision and use. It is expected that the framework once developed will be coordinated by national government and key national organisations to ensure that all participants can express their needs and requirements for successfully implementing climate services that serve the population of the country. The purpose of this consultative workshop was to provide a platform for various stakeholders (including WMO Permanent representatives and experts) from the ESA countries to enhance their capabilities in shaping their NFWWCS/NFCS for effective delivery of weather, water and climate services and reduce climate vulnerabilities in the sub-regions.